MODEL AREC DAN SOCIAL INSIGHT: STUDI EKSPERIMEN PADA PEMBELAJARAN SENI MUSIK KELAS IV SEKOLAH DASAR - Tendi Setiadi; Resa Respati; Rifqy Muhammad Hamzah (STKIP Subang, 2026)
Social insight is a key dimension of interpersonal intelligence that underpins students’ capacity to understand social situations and interact effectively with others. However, this capacity often remains suboptimal among elementary school students, necessitating intentional learning interventions. This study aims to examine the effect of the Auditory Repetition Exploration Creativity (AREC) Model on the Social insight of fourth-grade elementary school students in music education learning. A quantitative experimental approach with a posttest-only control group design was employed, involving 39 students in the experimental class and 39 students in the control class at SDN 1 Siluman, Tasikmalaya City, selected through saturated sampling. Data were collected using a Social insight instrument covering three dimensions: self-awareness, understanding of social situations and social ethics, and problem-solving skills. Data were analyzed using descriptive statistics and an Independent Sample t-test. The results showed that the mean Social insight score of the experimental class (45.56) was significantly higher than that of the control class (39.33). The t-test confirmed a highly significant difference (t = −7.409; p = 0.000 < 0.05), with the experimental class predominantly falling in the high category (89.74%) compared to the control class (23.08%). These findings demonstrate that the AREC Model has a significant positive effect on students’ Social insight in elementary school music education learning.